Employee Engagement in Information Technology Industry of Bengaluru City - Kumar, Dr. N. Srinivas (International Journal of Advanced Science and Technology, 2019)
Employee Engagement is an idea increasing critical significance in the previous 10 years. Association today utilize connected with representatives as a device for vital accomplice in the business. The idea of employee engagement has now increased much more significance, since numerous drivers have been recognized, which impact employee engagement at workplace. As IT companies across Learning, Feedback, Leadership, Colleague Empowerment, Team Work, Line Management and Communication well-being of employees will be one of the significant angles that HR managers need to tend spotlight on. Hence, employee engagement is today seen as a powerful source of competitive advantage in the turbulent times. The examination investigates the idea of employee engagement and also throws light on key drivers of employee engagement by analyzing specifically seven divers, namely Learning, Feedback, Leadership, Colleague Empowerment, Team Work, Line Management, and Communication. The available literature on drivers of employee engagement indicates that there is paucity of literature on these seven drivers and their impact on employee engagement. Thus, we focused on these seven specific and less researched drivers.